Optimization of methacrylated gelatin /layered double hydroxides nanocomposite cell-laden hydrogel bioinks with high printability for 3D extrusion bioprinting - ALARÇİN, EMİNE (My University, 2022)
Layered double hydroxides (LDHs) offer unique source of inspiration for design of bone mimetic biomaterials due to their superior mechanical properties, drug delivery capability and regulation cellular behaviors, particularly by divalent metal cations in their structure. Three-dimensional (3D) bioprinting of LDHs holds great promise as a novel strategy thanks to highly tunable physiochemical properties and shear-thinning ability of LDHs, which allow shape fidelity after deposition. Herein, we introduce a straightforward strategy for extrusion bioprinting of cell laden nanocomposite hydrogel bioink of gelatin methacryloyl (GelMA) biopolymer and LDHs nanoparticles. First, we synthesized LDHs by co-precipitation process and systematically examined the effect of LDHs addition on printing parameters such as printing pressure, extrusion rate, printing speed, and finally bioink printability in creating grid-like constructs. The developed hydrogel bioinks provided precise control over extrudability, extrusion uniformity, and structural integrity after deposition. Based on the printability and rheological analysis, the printability could be altered by controlling the concentration of LDHs, and printability was found to be ideal with the addition of 3 wt % LDHs. The addition of LDHs resulted in remarkably enhanced compressive strength from 652 kPa (G-LDH0) to 1168 kPa (G-LDH3). It was shown that the printed nanocomposite hydrogel scaffolds were able to support encapsulated osteoblast survival, spreading, and proliferation in the absence of any osteoinductive factors taking advantage of LDHs. In addition, cells encapsulated in G-LDH3 had a larger cell spreading area and higher cell aspect ratio than those encapsulated in G-LDH0. Altogether, the results demonstrated that the developed GelMA/LDHs nanocomposite hydrogel bioink revealed a high potential for extrusion bioprinting with high structural fidelity to fabricate implantable 3D hydrogel constructs for repair of bone defects.
Keywords: Biyomedikal Mühendisliği; Mühendislik ve Teknoloji; Biomedical Engineering; Engineering and Technology; MÜHENDİSLİK, BİYOMEDİKSEL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MALZEME BİLİMİ, BİYOMATERYAL; Malzeme Bilimi; ENGINEERING, BIOMEDICAL; ENGINEERING; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE, BIOMATERIALS; MATERIALS SCIENCE; Biyomalzemeler; Malzeme Bilimi (çeşitli); Genel Malzeme Bilimi; Genel Mühendislik; Biyomedikal mühendisliği; Mühendislik (çeşitli); Biyomühendislik; Fizik Bilimleri; Biomaterials; Materials Science (miscellaneous); General Materials Science; General Engineering; Engineering (miscellaneous); Bioengineering; Physical Sciences; 3D bioprinting; hydrogel bioink; layered double hydroxide; nanocomposite scaffold; GRAPHENE OXIDE; ALGINATE HYDROGELS; STEM-CELLS; NANOPARTICLES; LDH; AL; FABRICATION; SCAFFOLDS; DELIVERY; DESIGN